The Ecological Theology of the Indonesian Gayo Tribe: The Integration of Tawhīd Values into their Trade Tradition - Sukiman Sukiman (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2021)
This study analyzes the process of integration of tawhīd  (believing in one God) values with trade tradition among the Gayo tribe, which helped to improve their economy and create a more prosperous way of life. This tribe is domiciled in the central region of Aceh, whose origins are Old Malays, and they have lived for a long time in the highlands of Gayo. Thus, they were involved in typical economic activities such as farming, gardening, fishing,  rearing of livestock, as well as household businesses and tourism, which were carried out systemically and periodically by the government and jointly supervised by agricultural experts. However, every work carried out had monotheism values with an emphasis on faith and worship because all natural resources were believed to be owned by Allah SWT. This study uses a qualitative approach in which the data collected were in the form of words, images, and not numbers. Results revealed that by capitalizing on faith and piety, the Gayo tribe believes that they can achieve happiness and blessings like the people of Gayo Land who strictly practice Islam in their daily lives and have a blessed, prosperous and dignified life from God.